2012
DOI: 10.1093/ntr/nts252
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lapse in First Week of Smoking Abstinence in PTSD and Non-PTSD Smokers

Abstract: Results provide evidence of shorter time to first smoking lapse in PTSD, and add to evidence that early lapse occasions are more strongly related to trauma reminders, negative affect, and cravings in smokers with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 36 publications
1
75
0
Order By: Relevance
“…In addition, following trauma, smoking initiation and daily smoking rates also increased (Breslau et al, 2003, 2004). PTSD patients also showed lower rates of quitting (Hapke et al, 2005; Lasser et al, 2000), suffered from worse nicotine withdrawal symptoms (Dedert et al, 2011), and as a result showed shorter times to first smoking lapse (Beckham, Calhoun, Dennis, Wilson, & Dedert, 2012) than non-PTSD population. Similarly, patients with social phobia have also demonstrated increased rates of smoking initiation (Sonntag, Wittchen, Höfler, Kessler, & Stein, 2000).…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, following trauma, smoking initiation and daily smoking rates also increased (Breslau et al, 2003, 2004). PTSD patients also showed lower rates of quitting (Hapke et al, 2005; Lasser et al, 2000), suffered from worse nicotine withdrawal symptoms (Dedert et al, 2011), and as a result showed shorter times to first smoking lapse (Beckham, Calhoun, Dennis, Wilson, & Dedert, 2012) than non-PTSD population. Similarly, patients with social phobia have also demonstrated increased rates of smoking initiation (Sonntag, Wittchen, Höfler, Kessler, & Stein, 2000).…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…This is because while PTSD symptoms are reduced during nicotine intake (Beckham et al, 2005; Feldner et al, 2007; Greenberg et al, 2012; Thorndike et al, 2006), they resurface during abstinence (Dedert et al, 2011). Therefore, most PTSD patients reinitiate smoking to alleviate their symptoms (Beckham et al, 2012). However, while reinitiating smoking may help patients reduce their symptoms, Wilkinson and Gould’s (2013) results showing increased sensitivity to the effects of reintroduction of nicotine during nicotine withdrawal suggest that it may also enhance fear memories associated with new trauma and could prolong the course of the disorder.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…PTSD can be an impediment to successful quitting (Fu et al, 2007;Morris et al, 2014). Smokers with PTSD are more likely to relapse than smokers without PTSD (Beckham et al, 2013;Zvolensky et al, 2008). Hapke et al, (2005) found that trauma exposed persons with PTSD were significantly less likely to quit than individuals with no history of traumatic exposure; there was no significant difference in the odds of quitting among trauma exposed persons without PTSD compared to individuals with no history of traumatic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PTSD also appears to impair cessation success 6 . A recent study utilizing time sampling methodology found that smokers with PTSD had shorter time to lapse after a quit attempt relative to smokers without PTSD, and that those with PTSD were more likely to report negative affect as a situational factor (antecedent) to lapse 12 .…”
mentioning
confidence: 99%